Performance of Concrete Sheet Piles with Stranded Steel Waste Using Finite Element Method - Apriadi; Hery Awan Susanto; Dani Nugroho Saputro (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2026)
The innovation in precast industrial metal waste-based concrete materials aims to improve the mechanical properties of concrete while reducing its environmental impact. This study examined the performance of 62.25 MPa plain concrete sheet piles with the addition of steel fiber waste through finite element method (FEM)-based numerical modelling with a cantilever configuration that represents actual field conditions used linear modelling. The variations in the steel fiber waste content analyzed were 0%, 1%, 2%, 3%, and 4%. The test specimens were modelled with modified dimensions (50 × 20 × 10 cm) to accommodate the computational limitations. The material parameters refer to the SNI standard, where the elastic modulus of concrete is calculated using an empirical approach, and the steel fiber is modelled as an isotropic elastic material with mechanical properties according to the standard. The analysis focused on the deflection behavior, moment capacity, and deformation response to a design load of 41.5 kN. The simulation results showed that additional 1% strand content produced deflections that were within safe limits (≤ 2.8 mm). The lowest deflection value occurred in the 1% variation, with a decrease of 7.89% compared with normal concrete. Increasing the strand content above 1% did not provide significant additional benefits; in fact, at a content of 4%, the deflection increased by 5.57%. This indicates that an increase in fiber distribution density can reduce the homogeneity of concrete that potentially create weak zones in concrete. Thus, this study confirmed that adding 1% steel fiber waste is optimal for improving the flexural deformation performance of concrete sheet piles.